수도권 거주 결혼이주여성 가구의 식품환경과 식품불안정성 간의 관련성 - 육성민(Sung-Min Yook); 황지윤(Ji-Yun Hwang) (Journal of nutrition and health, 2023)
Purpose: Food environmental factors related to food insecurity affect household food intake in several socio-ecological aspects. This study explores the relationship between food environment factors and food insecurity in households with married immigrant women. Methods: From November 2018 to February 2020, a survey was conducted enrolling 249 married immigrant women residing in the metropolitan areas of South Korea. In the final analysis, 229 subjects were divided into 2 groups classified as food security (n = 154) and food insecurity (n = 75), as assessed by the score of food security. Three aspects of food environments were measured: built·natural, political·economic, and socio-cultural Results: Food environments were significantly different between food security and food insecurity groups, as follows: the number of foods market and their distance from the home and food status for the last week at home in the built·natural domain; monthly cost of food purchase and experience for food assistance in the political·economic domain; total score of social support, parenting, and cooking skills in the socio-cultural domain. A stepwise multivariate linear regression model showed a negative association between the food insecurity score with social support from family and food inventory status in the last week. After adjusting for confounders, a positive association was obtained between the experience of a food support program. The final regression model explains about 30% of the relationship obtained in the three food environment domains and food insecurity (p < 0.001). Conclusion: Not only economic factors, which are common determinants of household food insecurity, but socio-cultural factors such as social support also affect household food insecurity. Therefore, plans for implementing a food assistance program to improve food insecurity for households with immigrant women should consider financial support as well as other comprehensive aspects, including socio-cultural domain such as social support from family and community. 본 연구는 수도권에 거주하는 결혼이주여성 및 다문화가정을 대상으로 구조적·자연적, 정치적·경제적, 사회문화적 영역에서의 식품환경 요소들과 가구 식품불안정성 간의 연관성을 탐색하고자 하였다. 설문조사는 2018년 11월부터 2020년 2월까지 서울 및 수도권에 거주하는 중국, 베트남, 일본, 캄보디아, 몽골, 러시아, 대만 출신의 결혼이주여성 249명을 대상으로 실시되었다 (BE2018-34). 식품환경 요소는 구조적·자연적 영역에서 유용성과 접근성, 정치적·경제적 영역에서 가용성과 식품지원 및 영양교육 수혜 경험, 사회문화적 영역에서 영양지식, 조리능력, 양육방식, 가족과의 식사, 사회적 지지, 미디어의 영향력이 포함되었다. 가구 식품 불안정성은 국민건강영양조사의 식품안정성 측정 도구로 측정 및 계산되었다. 응답이 불충분하거나 식품불안정성 점수 산출이 어려운 경우를 제외한 229명을 대상으로 위계적 다중선형 회귀분석을 수행한 결과, 사회문화적 영역의 건강한 식생활에 대한 가족들의 사회적 지지가 가장 먼저 모델에 포함되었으며, 정치적·경제적 영역의 식품지원 서비스 수혜 경험 여부와 구조적·자연적 영역의 지난 1주일간 식품 보유 상황이 순서대로 추가되었다. 결과적으로 식품불안정성은 사회적 지지 및 식품 보유 상황과는 음의 연관성, 식품지원 서비스 수혜경험과는 양의 연관성이 있는 것으로 나타났다. 총 세 가지의 식품환경 요소가 포함된 최종회귀모델은 가구 식품불안정성에 대하여 약 30%를 설명하는 것으로 나타났다 (adjusted R2 = 0.298, p < 0.001). 이러한 결과를 통해 보편적으로 가구 식품불안정성의 영향 요인으로 알려져 있는 식품지원 수혜 경험과 같은 경제적 요인이나 식품 보유 상황과 같은 물리적 요인 이외에도 가족들의 건강한 식생활에 대한 사회적 지지가 가구 식품불안정성과 연관될 수 있다는 사실을 확인하였다. 따라서, 본 연구의 결과는 다문화가정의 가구 식품불안정성 개선을 위한 정책적 지원 프로그램이 경제적 측면뿐만 아니라 가족 간 관계나 가족 및 지역사회로부터의 사회적 지지 등 사회문화적 측면까지 포괄적으로 고려하여 기획되어야 함을 시사한다.